Handwritten Bangla character recognition to braille pattern conversion using image processing and machine learning - Abir, Tawhidur Rahman; Ahmed, Touseef Saleh Bin; Rahman, Md. Tausif; Jafreen, Sumaiya (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.